Langues, ethnies et territoires à Addis-Abeba : la diversité langagière comme indicateur des mutations urbaines - Véronique Miguel Addisu (Territoire en Mouvement)
This sociolinguistic study focus on ethnic groups and first languages declared in Addis Ababa during the last two national censuses (1994 and 2007). Data show that linguistic diversity and ethnic groups listed increases while Amharic, vehicular language in town, remains declared by approximately 70 % of the speakers in both censuses. In 2007, the answers vary widely according to the groups of subcities (central or peripheral) either according to their ethnic groups and their size. Crossing of all these factors enhances various tendencies: first languages and ethnic memberships are differently surrounded according to the groups in these two spaces, while the socioeconomic data do not vary much. These results suggest that minority languages do not disappear for the benefit of a single language, which would be the unique condition of an urban development. They participate more and more in the structuring of socioeconomic networks differentiated in the city, while social inequalities are increasing for decades.